Genetic variation and host–parasite specificity of Striga resistance and tolerance in rice: the need for predictive breeding - Rodenburg, J.; Cissoko, M.; Kayongo, N.; Dieng, I.; Bisikwa, J.; Irakiza, R.; Masoka, I.; Midega, C.A.O.; Scholes, J.D. (Wiley, 2017)
The parasitic weeds Striga asiatica and Striga hermonthica cause devastating yield losses to upland rice in Africa. Little is known about genetic variation in host resistance and tolerance across rice genotypes, in relation to virulence differences across Striga species and ecotypes. Diverse rice genotypes were phenotyped for the above traits in S. asiatica‐ (Tanzania) and S. hermonthica‐infested fields (Kenya and Uganda) and under controlled conditions. New rice genotypes with either ecotype‐specific or broad‐spectrum resistance were identified. Resistance identified in the field was confirmed under controlled conditions, providing evidence that resistance was largely genetically determined. Striga‐resistant genotypes contributed to yield security under Striga‐infested conditions, although grain yield was also determined by the genotype‐specific yield potential and tolerance. Tolerance, the physiological mechanism mitigating Striga effects on host growth and physiology, was unrelated to resistance, implying that any combination of high, medium or low levels of these traits can be found across rice genotypes. Striga virulence varies across species and ecotypes. The extent of Striga‐induced host damage results from the interaction between parasite virulence and genetically determined levels of host–plant resistance and tolerance. These novel findings support the need for predictive breeding strategies based on knowledge of host resistance and parasite virulence.The parasitic weeds Striga asiatica and Striga hermonthica cause devastating yield losses to upland rice in Africa. Little is known about genetic variation in host resistance and tolerance across rice genotypes, in relation to virulence differences across Striga species and ecotypes.Diverse rice genotypes were phenotyped for the above traits in S. asiatica‐ (Tanzania) and S. hermonthica‐infested fields (Kenya and Uganda) and under controlled conditions.New rice genotypes with either ecotype‐specific or broad‐spectrum resistance were identified. Resistance identified in the field was confirmed under controlled conditions, providing evidence that resistance was largely genetically determined. Striga‐resistant genotypes contributed to yield security under Striga‐infested conditions, although grain yield was also determined by the genotype‐specific yield potential and tolerance. Tolerance, the physiological mechanism mitigating Striga effects on host growth and physiology, was unrelated to resistance, implying that any combination of high, medium or low levels of these traits can be found across rice genotypes.Striga virulence varies across species and ecotypes. The extent of Striga‐induced host damage results from the interaction between parasite virulence and genetically determined levels of host–plant resistance and tolerance. These novel findings support the need for predictive breeding strategies based on knowledge of host resistance and parasite virulence.